A questionnaire based study of prevailing teaching methods in pharmacology and its efficacy /evaluation by second professional M.B.B.S students - Pukhta, Muzaffar Ahmad; Bhat, Mohammad Younis; Singh, Zorawar (International Journal of Research in Medical Sciences, 2017)
Background: Pharmacology is the subject which has got scientific obligation and feedback from the students facilitates a change in preconceived notion about teaching. The study was under taken to elicit the perception and feedback regarding the prevailing system of teaching methods in pharmacology and requirement of any consequent changes. Methods: A questionnaire was designed and given to second years medical students on internationally accepted Likert scale which they were supposed to fill after giving due instructions. Analysis was done on percentage wise distribution of various parameters used in the questionnaire. Results: Out of the total of 150 enrolled students, 130 filled and returned questionnaire with students vouching for various changes with 125 (96%) agreeing that black board teaching as best method of teaching in contrast to 31 (23.8%) for PPT and 87 (66.9%) for combination of both. 109 (83.8%) wanted distribution of handouts giving outline of topic before lecture classes. Conclusions: There is a need of various reforms for improvement of prevailing teaching methods in pharmacology like microteaching and group discussions and involving MCQs in pattern of evaluation as opined by the students.